2016
DOI: 10.1002/smi.2735
|View full text |Cite
|
Sign up to set email alerts
|

Financial strain, dyadic coping, relationship satisfaction, and psychological distress: A dyadic mediation study in Greek couples

Abstract: Financial strain typically has a severe impact on a couple's functioning and the well-being of its members. In this study, we examined the indirect relation of financial strain to partners' relationship satisfaction and psychological distress, using dyadic coping as a mediator, in a sample of Greek couples. One hundred and eighteen couples participated in a cross-sectional study. Perceived material loss in the past and perceived threat of loss in the future were used as financial strain indices. The actor-part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 44 publications
4
24
0
4
Order By: Relevance
“…Studies have been approached the relationship between stressful life events and psychological problems in two ways. One group of studies examined the relationship between a single type of stressful life events (e.g., financial problems, social relations, and family conflicts) and a number of psychological problems or symptoms [ 19 , 20 , 26 28 ]. The second group of studies has relied on composite measures of stressful life events, because a number of these events overlap with each other or can conceptually be combined together [ 29 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have been approached the relationship between stressful life events and psychological problems in two ways. One group of studies examined the relationship between a single type of stressful life events (e.g., financial problems, social relations, and family conflicts) and a number of psychological problems or symptoms [ 19 , 20 , 26 28 ]. The second group of studies has relied on composite measures of stressful life events, because a number of these events overlap with each other or can conceptually be combined together [ 29 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a Romanian National Survey (Barometrul de Opinie Publica, 2007), both men and women reported economic strain as being the most important variable in generating family conflicts and the financial situation was found to be one of the main explanatory variables of marital satisfaction. Moreover, Karademas and Roussi (2016) found that DC mediated the association between economic strain and marital satisfaction in a sample of…”
Section: Economic Strain and Supportive Dyadic Coping In Couplesmentioning
confidence: 99%
“…Economic strain, in particular, has been found to decrease people's ability to provide social and emotional support to their partners (e.g., providing help, expressing care, giving encouragement, showing affection, and positive dyadic coping [DC]) and to increase undermining behaviours (e.g., criticizing, insulting, and negative DC; Karademas & Roussi, 2016;Simons, Lorenz, Wu, & Conger, 1993;Vinokur, Price, & Caplan, 1996). A daily diary study indicated that individuals experiencing negative daily financial events reported more negative interpersonal events on the same day (with family members and with a romantic partner; Sturgeon, Zautra, & Okun, 2014).…”
Section: Economic Strain and Supportive Dyadic Coping In Couplesmentioning
confidence: 99%
See 2 more Smart Citations